Corporate social responsibility in Mauritius: an analysis of annual reports of multinational hotel groups - Ourvashi Bissoon (Asian Journal of Sustainability and Social Responsibility (AJSSR), 2018)
The purpose of this paper is to ascertain the level of CSR reporting of the top multinational hotel groups in Mauritius. Content analysis method is used to identify the social responsibility patterns found in their annual reports. This study thus investigates the level and the reasons for CSR disclosure of multinational groups in the hospitality sector in Mauritius through a review of their annual reports. The aim is to explore the possibility of using the legitimacy theory as a plausible explanation for CSR reporting practices by multinational hotel groups in the context of a developing country. Mauritius proves to be an interesting case study as the hotel industry is one of the main engines of growth and the country is also actively trying to attract foreign investors in terms of FDI and multinational enterprises (MNEs). Furthermore, the country has also made it mandatory for profit making entities to devote 2% of their book profits to CSR activities since 2009. The annual reports of 6 hotel groups have been analysed using the Global Reporting Initiative (GRI) indicators. The study shows that CSR reporting is prevalent among all the hotel groups in the sample but there is no primary area of CSR focus in the sector. The emphasis placed on CSR also varies significantly. Furthermore, the majority of the CSR information tend to relate to particular categories showing that the hotel groups take a narrow view of CSR and tend to prioritise particular areas at the expense of others. The findings also suggest that the disclosures tend to have a public-relations bias, with 'good news' type of disclosures being mostly dominant while 'bad news' disclosures tend to be minimal. The findings thus provide some support for legitimacy theory in explaining CSR disclosures.
Keywords: 650; Corporate Social Responsibility; Berichtswesen; Regulierung; Selbstverpflichtung; Multinationales Unternehmen; Hotellerie; Mauritius